SIMULASI DOCKING KURKUMIN ENOL, BISDEMETOKSIKURKUMIN DAN ANALOGNYA SEBAGAI INHIBITOR ENZIM12-LIPOKSIGENASE - Gita Syahputra (Jurnal Biofisika, 2014)
Docking simulations of curcumin and its analogs have been conducted on 12-Lipoxygenase receptor enzyme. Semi-flexibledocking simulation has been performed using AutoDock Vina.This research is aimed to find the most stable compounds of curcumin that bind with 12-Lipoxygenase enzyme. Ligands used in this research consist of enol curcumin, bisdemetoxycurcumin, and two analogs (analog A and B). Gibbs free energy and the type of chemical bonding and binding sites of ligand-receptor docking aresome of the results discussed in this paper. All.simulation results of curcumin and its analogs have shown lower binding affinitycompared to arachidonate acid (natural ligand of 12-Lipoxygenase) and ibuprofen which act as competitive inhibitors.Enol curcumin has been found tohave the best score of Gibbs free energy ∆G = -8.4 kcal/mol. Overall curcumin and its analogs have shown potential as stable Inhibitors for 12-Lipoxygenase and able to block the production of Leukotrien and 12-HETE which responsible for inflammation.